Employer branding : improving employer attractiveness the case of winning scientific management - Figueira, Joana Coelho (2019)
The competitive environments industries are currently living have given rise to a war for talented employees. Therefore, companies have been giving an increasing importance to investing resources and efforts in strategies that empower their employer brands in order to become more attractive as an employer. Employer branding is the process of creating a desirable employer image through brand marketing strategies, which will be promoted both internally and externally. The aim of this dissertation is to understand what are the areas of improvement in Winning Scientific Management employer branding activities in order to develop a more attractive employer brand, and to give some recommendations on which steps could the company make. Hence, this dissertation made use of past literature about employer branding and some empirical analysis to provide recommendations to Winning Scientific Management. The above cited empirical analysis developed made use of some data provided by the client as well as the results of a survey ran among the organization’s employees. The main findings of this dissertation were that Winning needs to redirect its resources and efforts in order to be more effective in recruiting the talented employees required for its business activities as well as being perceived as an employer of choice.